Bacillus cabrialesii BH5 Protects Tomato Plants Against Botrytis cinerea by Production of Specific Antifungal Compounds - Zhou, Lu; Song, Chunxu; Muñoz, Claudia Y.; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
The gray mold caused by the phytopathogen Botrytis cinerea presents a threat to global food security. For the biological regulation of several plant diseases, Bacillus species have been extensively studied. In this work, we explore the ability of a bacterial strain, Bacillus cabrialesii BH5, that was isolated from tomato rhizosphere soil, to control the fungal pathogen B. cinerea. Strain B. cabrialesii BH5 showed a strong antifungal activity against B. cinerea. A compound was isolated and identified as a cyclic lipopeptide of the fengycin family by high-performance liquid chromatography and tandem mass spectrometry (ESI-MS/MS) that we named fengycin H. The fengycin H-treated hyphae of B. cinerea displayed stronger red fluorescence than the control, which is clearly indicating that fengycin H triggered the hyphal cell membrane defects. Moreover, root inoculation of tomato seedlings with BH5 effectively promoted the growth of tomato plants. Transcription analysis revealed that both BH5 and fengycin H stimulate induced systemic resistance of tomato plants via the jasmonic acid signaling pathway and provide a strong biocontrol effect in vivo. Therefore, the strain BH5 and fengycin H are very promising candidates for biological control of B. cinerea and the associated gray mold.